Pattern recognition: 30th DAGM symposium Munich, Germany, June 10-13, 2008 proceedings - Rigoll, Gerhard (Lecture notes in computer science, 2008)
Learning and Classification -- MAP-Inference for Highly-Connected Graphs with DC-Programming -- Approximate Parameter Learning in Conditional Random Fields: An Empirical Investigation -- Simple Incremental One-Class Support Vector Classification -- A Multiple Kernel Learning Approach to Joint Multi-class Object Detection -- Fast Generalized Belief Propagation for MAP Estimation on 2D and 3D Grid-Like Markov Random Fields -- Boosting for Model-Based Data Clustering -- Improving the Run-Time Performance of Multi-class Support Vector Machines -- Sliding-Windows for Rapid Object Class Localization: A Parallel Technique -- A Performance Evaluation of Single and Multi-feature People Detection -- Tracking -- Model-Based Motion Capture for Crash Test Video Analysis -- Efficient Tracking as Linear Program on Weak Binary Classifiers -- A Comparison of Region Detectors for Tracking -- Combining Densely Sampled Form and Motion for Human Action Recognition -- Recognition and Tracking of 3D Objects -- Medical Image Processing and Segmentation -- Segmentation of SBFSEM Volume Data of Neural Tissue by Hierarchical Classification -- Real-Time Neighborhood Based Disparity Estimation Incorporating Temporal Evidence -- A Novel Approach for Detection of Tubular Objects and Its Application to Medical Image Analysis -- Weakly Supervised Cell Nuclei Detection and Segmentation on Tissue Microarrays of Renal Clear Cell Carcinoma -- A Probabilistic Segmentation Scheme -- Using Eigenvalue Derivatives for Edge Detection in DT-MRI Data -- Space-Time Multi-Resolution Banded Graph-Cut for Fast Segmentation -- Combination of Multiple Segmentations by a Random Walker Approach -- Audio, Speech and Handwriting Recognition -- Automatic Detection of Learnability under Unreliable and Sparse User Feedback -- Novel VQ Designs for Discrete HMM On-Line Handwritten Whiteboard Note Recognition -- Switching Linear Dynamic Models for Noise Robust In-Car Speech Recognition -- Natural Language Understanding by Combining Statistical Methods and Extended Context-Free Grammars -- Multiview Geometry and 3D-Reconstruction -- Photoconsistent Relative Pose Estimation between a PMD 2D3D-Camera and Multiple Intensity Cameras -- Implicit Feedback between Reconstruction and Tracking in a Combined Optimization Approach -- 3D Body Scanning in a Mirror Cabinet -- On Sparsity Maximization in Tomographic Particle Image Reconstruction -- Resolution Enhancement of PMD Range Maps -- A Variational Model for the Joint Recovery of the Fundamental Matrix and the Optical Flow -- Motion and Matching -- Decomposition of Quadratic Variational Problems -- A Variational Approach to Adaptive Correlation for Motion Estimation in Particle Image Velocimetry -- Optical Rails -- Postprocessing of Optical Flows Via Surface Measures and Motion Inpainting -- An Evolutionary Approach for Learning Motion Class Patterns -- Relative Pose Estimation from Two Circles -- Staying Well Grounded in Markerless Motion Capture -- An Unbiased Second-Order Prior for High-Accuracy Motion Estimation -- Physically Consistent Variational Denoising of Image Fluid Flow Estimates -- Convex Hodge Decomposition of Image Flows -- Image Analysis -- Image Tagging Using PageRank over Bipartite Graphs -- On the Relation between Anisotropic Diffusion and Iterated Adaptive Filtering -- Comparing Local Feature Descriptors in pLSA-Based Image Models -- Example-Based Learning for Single-Image Super-Resolution -- Statistically Optimal Averaging for Image Restoration and Optical Flow Estimation -- Deterministic Defuzzification Based on Spectral Projected Gradient Optimization -- Learning Visual Compound Models from Parallel Image-Text Datasets -- Measuring Plant Root Growth -- A Local Discriminative Model for Background Subtraction -- Perspective Shape from Shading with Non-Lambertian Reflectance -- The Conformal Monogenic Signal.
Includes bibliographical references and index